Utilization of Living Pharmacy in Overcoming Stunting in Tanjung Batu Seberang Village - Susi Dewiyeti; Bonita Hirza; Refi Elvira Yuliani; Rieno Septra Nery; Heru Heru; Luvi Antari; Surismiati Surismiati; Supriatini Supriatini; Samsilayurni Samsilayurni (Asosiasi Profesi Multimedia Indonesia, 2024)
The overall objective of this community service activity is to empower the community through the use of medicinal plant gardens as one of the efforts to address stunting in Tanjung Batu Seberang Village, Tanjung Batu Subdistrict, Ogan Ilir Regency, South Sumatra. Specifically, this activity aims to: (1) provide a deeper understanding of the importance of health, (2) explain the various types of medicinal plants that can be used to improve health, particularly in combating stunting, and (3) change the community's mindset regarding the importance of health quality. The approach used in this activity is a descriptive qualitative method. The implementation of the activity is divided into three phases: first, administering pre-test and post-test questionnaires to assess participants' initial and final understanding; second, delivering materials on the use of medicinal plant gardens to address stunting; and third, providing training on planting medicinal plants. The subjects of this activity are 50 residents of Tanjung Batu Seberang Village. The instruments used are pre-test and post-test questionnaires, with the activity conducted in one day. The results show that 86.50% of participants understand basic health concepts, 92.54% can explain the types of medicinal plants that could potentially combat stunting, and 91.51% experienced a shift in mindset regarding health quality. In conclusion, this training provides practical solutions and motivation for the community to adopt healthier lifestyles, particularly in maintaining children's nutrition by utilizing processed plants as a source of nutritious food, thus improving nutritional status and the overall quality of life in Tanjung Batu Seberang Village.